Minnesota municipal utility uses GIS to benefit 82,000 customers. (American City & County, 2015)
The article discusses how Rochester Public Utilities (RPU) in Rochester, Minnesota is using an enterprise geographic information system (GIS) program called ArcGIS ArcMap from Esri to display geographical and tabular data during power and water service interruptions.